Measurement of Cadmium Ion in the Presence of Metal-Binding Biopolymers in Aqueous Sample. (8th September 2013) - Pu, Jian; Fukushi, Kensuke
Abstract : In aqueous environment, water-soluble polymers are effectively used to separate free metal ions from metal-polymer complexes. The feasibilities of four different analytical techniques, cadmium ion-selective electrode, dialysis sack, chelate disk cartridge, and ultrafiltration, in distinguishing biopolymer-bound and nonbound cadmium in aqueous samples were investigated. And two different biopolymers were used, including bovine serum albumin (BSA) and biopolymer solution extracted from cultivated activated sludge (ASBP). The ISE method requires relatively large amount of sample and contaminates sample during the pretreatment. After the long reaction time of dialysis, the equilibrium of cadmium in the dialysis sack would be shifted. Due to the sample nature, chelate disk cartridge could not filter within recommended time, which makes it unavailable for biopolymer use. Ultrafiltration method would not experience the difficulties mentioned above. Ultrafiltration method measuring both weakly and strongly bound cadmium was included in nominally biopolymer-cadmium complex. It had significant correlation with the Ion-selective electrode (ISE) method (R 2 = 0.989 for BSA, 0.985 for ASBP).